Renal Mitochondrial Cytopathies - Francesco Emma; Giovanni Montini; Leonardo Salviati; Carlo Dionisi-Vici (International Journal of Nephrology)
Renal diseases in mitochondrial cytopathies are a group of rare diseases that are characterized by frequent multisystemic involvement and extreme variability of phenotype. Most frequently patients present a tubular defect that is consistent with complete De Toni-Debré-Fanconi syndrome in most severe forms. More rarely, patients present with chronic tubulointerstitial nephritis, cystic renal diseases, or primary glomerular involvement. In recent years, two clearly defined entities, namely 3243 A > G tRNALEU mutations and coenzyme Q10 biosynthesis defects, have been described. The latter group is particularly important because it represents the only treatable renal mitochondrial defect. In this paper, the physiopathologic bases of mitochondrial cytopathies, the diagnostic approaches, and main characteristics of related renal diseases are summarized.